2021
DOI: 10.3390/ani11113261
|View full text |Cite
|
Sign up to set email alerts
|

Clostridium butyricum Improves Rumen Fermentation and Growth Performance of Heat-Stressed Goats In Vitro and In Vivo

Abstract: This study aimed to evaluate the effects of Clostridium butyricum on rumen fermentation and the growth performance of heat-stressed goats. The in vitro fermentation was carried out using Clostridium butyricum supplement at 0% (CG), 0.025% (CB1), 0.05% (CB2), 0.10% (CB3), and 0.20% (CB4) of the dry matter (DM) weight of basal diet. Results showed that ruminal pH and the concentrations of ammonia nitrogen, total volatile fatty acids, acetic acid, propionic acid, as well as the acetic acid to propionic acid ratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 28 publications
3
22
0
Order By: Relevance
“…The greater butyrate proportion with C. butyricum than control at low media pH or with medium and high (trend) dose of C. butyricum at high pH explained the production of butyrate by C. butyricum . The increased concentrations of NH 3 -N with supplementation of C. butyricum at either media pH 6.0 or pH 6.6 compared with control in the current study is consistent with Cai et al ( 2021 ). Those authors found an increase in the rumen NH 3 -N concentration with supplemented C. butyricum both in in vitro and in vivo , suggesting that supplementation of C. butyricum enhanced the microbial proteolytic activity in the rumen.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…The greater butyrate proportion with C. butyricum than control at low media pH or with medium and high (trend) dose of C. butyricum at high pH explained the production of butyrate by C. butyricum . The increased concentrations of NH 3 -N with supplementation of C. butyricum at either media pH 6.0 or pH 6.6 compared with control in the current study is consistent with Cai et al ( 2021 ). Those authors found an increase in the rumen NH 3 -N concentration with supplemented C. butyricum both in in vitro and in vivo , suggesting that supplementation of C. butyricum enhanced the microbial proteolytic activity in the rumen.…”
Section: Discussionsupporting
confidence: 92%
“…In the current study, the quadratically changed GP kinetics and DMD (numerically) with increasing supplementation of C. butyricum at high media pH appeared to be consistent with the report by Cai et al ( 2021 ) who found greater in vitro rumen digestibilities of DM and NDF with medium and medium-high doses of C. butyricum addition, but lower digestibilities of DM and NDF with high dose. The media pH was also higher with medium than high doses of C. butyricum in the study of Cai et al ( 2021 ). These results suggest that high media pH would favor the activity of C. butyricum in the rumen, which might explain the positive effect of C. butyricum on GP and DMD at media pH 6.6 but not at media pH 6.0 in the present study.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations